The Influence of Nurse's Therapeutic Approach on the Patient Healing Process - Susi Susanti; Nur Ambiya (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: The patient's healing process is influenced not only by physical medical and nursing procedures, but also by psychological and emotional factors. A therapeutic approach by nurses, which includes empathetic communication, emotional support, and a trusting relationship, is believed to help improve the patient's response to treatment and accelerate the healing process. Objective: This study aims to analyze the influence of nurses' therapeutic approaches on the patient's healing process. Method: This study used a quantitative design with a descriptive analytical approach and cross-sectional method. The study sample consisted of 80 inpatients at Hospital X selected using purposive sampling technique. Data were collected using a nurse therapeutic approach questionnaire and patient healing process indicators, then analyzed using the Chi- Square test with a significance level of α = 0.05. Results: The results showed that most respondents rated the nurse therapeutic approach in the good category (67.5%) and most patients experienced a good healing process (70.0%). The results of statistical tests showed a significant influence between the nurse therapeutic approach on the patient healing process (p = 0.001). Conclusion: The nurse therapeutic approach has a significant influence on the patient healing process. Therefore, the application of the therapeutic approach needs to be improved as an integral part of nursing care to support patient healing holistically.